Proton beam therapy – the challenges of delivering high-quality evidence of clinical benefit - National Cancer Research Institute Clinical and Translational Radiotherapy Research Working Group; (CTRad) Proton Beam Clinical Trial Strategy Group; Amos, R; Bulbeck, H; Burnet, N; Crellin, A; Eaton, D; Evans, P; Hall, E; Hawkins, M; Kirby, K; Mackay, R; et al. (Elsevier, 2018)
The use of proton beam therapy (PBT) offers the opportunity to improve greater conformality of radiotherapy treatment delivery in some patients. However, it is associated with a high capital cost and the need to build new dedicated facilities. We discuss how the global radiotherapy community can respond to the challenge of producing high-quality evidence of clinical benefit from PBT in adult patients. In the UK, the National Cancer Research Institute-funded Clinical and Radiotherapy Translational group has established the PBT Clinical Trial Strategy Group. An eight-point framework is described that can assist the development and delivery of high-quality clinical trials.